2009
DOI: 10.3748/wjg.15.1420
|View full text |Cite
|
Sign up to set email alerts
|

Individually administered or co-prescribed thiopurines and mesalamines for inflammatory bowel disease

Abstract: Data from both basic research and clinical experience continue to suggest that mesalamines and thiopurines are effective and efficient for the maintenance of remission of inflammatory bowel diseases. Several decades following the formalization of their indications, attention on these two drugs has been fostered by recent achievements. Demonstration of the ability of mesalamine to activate a colonocyte differentiation factor has shed light on its chemopreventive effects on colorectal cancer; in addition to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Combination of AZA or MP with aminosalicylates is very common in clinical practice 61. Many studies have found that aminosalicylates increase 6TGN levels in a majority of the patients, although whether or not this increase has clinical significance still remains controversial.…”
Section: Monitoring Thiopurine Metabolitesmentioning
confidence: 99%
“…Combination of AZA or MP with aminosalicylates is very common in clinical practice 61. Many studies have found that aminosalicylates increase 6TGN levels in a majority of the patients, although whether or not this increase has clinical significance still remains controversial.…”
Section: Monitoring Thiopurine Metabolitesmentioning
confidence: 99%
“…89,90 Addition of 5-ASA to thiopurine therapy led to increase in total 6-TGN levels in 82% of study patients in 1 study and 100% in another study. 89,90 Addition of 5-ASA to thiopurine therapy led to increase in total 6-TGN levels in 82% of study patients in 1 study and 100% in another study.…”
Section: Sulfasalazine and Mesalamine Can Alter Thiopurine Metabolitesmentioning
confidence: 94%
“…Several studies indicate that 5-ASAs may influence the metabolism of thiopurines [106][107][108][109]. This is important, as 71% of patients with IBD established on thiopurines are coprescribed 5-ASAs [109].…”
Section: -Aminosalicylic Acidmentioning
confidence: 98%
“…Several studies indicate that 5-ASAs may influence the metabolism of thiopurines [106][107][108][109]. This is important, as 71% of patients with IBD established on thiopurines are coprescribed 5-ASAs [109]. A recent retro spective ana lysis has shown that administration of concomitant 5-ASA (3 g/day mesalazine) leads to significantly higher TGN levels in comparison with patients prescribed AZA/MP alone, and is a risk factor for myelotoxicity (odds ratio: 3.45; 95% CI: 1.31-9.04; p = 0.01) [110].…”
Section: -Aminosalicylic Acidmentioning
confidence: 99%